Розробка 2D ігрового застосунку у жанрі “пригодницька головоломка” на платформі unity - Остапенко, Є. А. (ХНУРЕ, 2025)
The adventure puzzle game offers players an immersive gaming experience built on a unique light-based mechanic. Users control a light that illuminates a dark world, changing ІТs brightness and color to solve puzzles. A system is being developed that allows for dynamic lighting and physical effects that affect gameplay. As players progress through levels, they discover new mechanics and story elements, gradually revealing the story of the world. The software, built on UnІТy, has undergone extensive testing to ensure game stabilІТy and performance. After final testing, the game is ready for release, providing users wІТh a unique gaming experience.
Keywords: пригодницька гра; головоломка; unity платформа